High‐resolution ultrasound biomicroscopy as an adjunctive diagnostic tool for anterior scleral inflammatory disease. (19th February 2016) - Zur, Dinah; Neudorfer, Meira; Shulman, Shiri; Rosenblatt, Amir; Habot‐Wilner, Zohar
Abstract: Purpose: To study high‐resolution ultrasound biomicroscopy (UBM) findings in anterior scleral inflammatory disease and evaluate the efficacy of high‐resolution UBM as an adjunctive diagnostic tool. Methods: A cross‐sectional study. The medical records of 30 patients (33 eyes) with episcleritis or anterior scleritis were reviewed for clinical features and high‐resolution UBM findings. Ultrasound biomicroscopy (UBM) examination was performed using 50 MHz Aviso S (Quantel Medical, Clermont‐Ferrand, France). Results: Seventeen eyes had episcleritis [nodular (12), simple (five)], and 16 eyes had anterior scleritis [nodular (14), diffuse (two)] as classified by UBM. The use of high‐resolution UBM allowed high‐resolution imaging of the sclera and episclera and showed characteristic patterns of episcleritis and anterior scleritis. The clinical classification matched UBM findings in 25 (76%) eyes. In the other eight eyes (24%), UBM analysis led to a change in the final classification: four eyes with suspected episcleritis were classified with scleritis, and four eyes with suspected scleritis were classified with episcleritis. Eleven patients (36.7%) had an associated systemic disease. Conclusion: High‐resolution UBM enabled visualization of distinct imaging findings of episcleritis and anterior scleritis, indicating its usefulness in the classification of challenging cases of anterior scleral inflammatory disease.